BLOOD TYPE O IS A RISK FACTOR FOR HYPERFIBRINOLYSIS AND MASSIVE TRANSFUSION AFTER SEVERE INJURY. Issue 6 (21st December 2022) - DeBot, Margot; Eitel, Andrew P.; Moore, Ernest E.; Sauaia, Angela; Lutz, Patrick; Schaid, Terry R.; Hadley, Jamie B.; Kissau, Daniel J.; Cohen, Mitchell J.; Kelher, Marguerite R.; Silliman, Christopher C.
ABSTRACT: Background: Blood type O is the most common blood type and has lower von Willebrand factor (vWF) levels (25%–35% lower than non-O blood types). von Willebrand factor is important for initiating platelet attachment and binding factor VIII. We hypothesized that patients with type O blood are at an increased risk of trauma-induced coagulopathy and bleeding post injury. Study Design: Adult trauma activations with known blood type at a level I trauma center with field systolic blood pressure < 90 mm Hg were studied retrospectively. The relationships of blood group O versus non-O to coagulation assays, massive transfusion (MT), ventilator-free days, and mortality were adjusted for confounders. Hyperfibrinolysis (HF) was defined as thromboelastogram of percent lysis in 30 min > 3%, and fibrinolysis shutdown was defined as percent lysis in 30 min < 0.9%. von Willebrand factor activity was quantified on 212 injured patients using a STAGO apparatus. Results: Overall, 268 patients met criteria. Type O patients were more likely to develop HF than non–type O blood patients (43% vs. 29%, P = 0.06) and had significantly lower vWF activity (222% vs. 249%, P = 0.01). After adjustment for New Injury Severity Score and blunt mechanism, type O had higher odds of HF (odds ratio, 1.94, 95% confidence interval, 1.09–3.47) and increased odds of MT (odds ratio, 3.02; 95% confidence interval, 1.22–7.49). Other outcomes were not significantly affected. Conclusion: Type O patients with hypotension had increased HF and MT post injury, and these were associated with lower vWF activity. These findings have implications for the monitoring of HF in patients receiving type O whole-blood transfusions post injury.